Uncovering key patterns in self-harm in adolescents: sequence analysis using the card sort task for self-harm (CaTS) - Townsend, Ellen; Wadman, Ruth; Sayal, Kapil; Armstrong, M.; Harroe, C.; Majumder, P.; Vostanis, P.; Clarke, David (Elsevier, 2016)
Background